Influence of the underneath cavity on buoyant-forced cooling of the integrated photovoltaic panels in building roof: a thermography study - Mirzaei, Parham A.; Carmeliet, Jan (Wiley, 2015)
Airflow around building-integrated photovoltaics (BIPV) has a significant impact on their hygrothermal behavior and degradation. The potential of reducing the temperature of BIPV using an underneath cavity is experimentally and numerically investigated in literature. Most of the models are oversimplified in terms of modeling the impact of 3D flow over/underneath of PV modules, which can result in a non-uniform surface temperature and consequently a non-homogenous thermal degradation. Moreover, the simultaneous presence of radiation and convection related to upstream wind, in addition to the combined impact of back-ventilation and surface convection, is barely addressed in literature. However, these simplifications can result in the unrealistic loading climate conditions. This paper aims to present a unique experimental setup to provide more realistic climate conditions for investigating the ventilation potential of the underneath. The setup consists of a solar simulator and a building prototype with installed PV, placed inside an atmospheric wind tunnel to control upstream wind velocity. Thermography is performed using an infrared camera to monitor the surface temperature of the BIPV. The potential of an underneath cavity with various cavity heights and PV arrangement is further investigated in this paper. The outcome would be eventually useful in the development of practical guidelines for BIPV installation. Copyright © 2013 John Wiley & Sons, Ltd.